Islam Concept about Tolerance and Religious Freedom - Rahmawati Caco (Al-Ulum, 2014)
The discourse of tolerance and religious freedom become the impossibility which cannot be escaped in our plural society life. The main problem is how the concept al-Qur’an in explaining well the case of tolerance and religious freedom. Religious freedom naturally is the foundation for creating religion harmony between religious followers. Without religious freedom, it is impossible to create religion harmony. Religious freedom is the right of every people. The right to convey God is given, and nobody can take it out. Tolerance, freedom, and religion plurality implicitly and explicitly contain in al-Qur’an. The confirmation of al-Qur’an about social group plurality and life necessity amomg groups are developed without limitationas long as have benefits. The acknowledgement of al-Qur’an about social group plurality and the human necessity life is guided without limitation as long as it has profit and benefit. In the case of aqidah and belief, al-Qur’an contains very absolute boarded and there is no bargain, because belief and faith is the case relation between human and their Creature.